Our Australian girl - Hamer, Michelle (Puffin, 2014)
It's 1930 and Daisy has been adopted and whisked away to a beautiful mansion. She's to be a companion to Annie, a girl with a mysterious illness. While Daisy's new life is full of luxuries she could never have imagined, what she wants the most is the thing her new parents can't provide: the freedom to find her real family before it's too late ... Follow Daisy on her adventure in the third of four exciting stories about a hopeful girl in troubled times